The Arabidopsis R2R3 MYB Proteins FOUR LIPS and MYB88 Restrict Divisions Late in the Stomatal Cell Lineage - Lai, Lien B. (American Society of Plant Biologists, 2005)
The two guard cells of a stoma are produced by a single symmetric division just before terminal differentiation. Recessive mutations in the FOUR LIPS (FLP) gene abnormally induce at least four guard cells in contact with one another. These pattern defects result from a persistence of precursor cell identity that leads to extra symmetric divisions at the end of the cell lineage. FLP is likely to be required for the correct timing of the transition from cell cycling to terminal differentiation. FLP encodes a two-repeat (R2R3) MYB protein whose expression accumulates just before the symmetric division. A paralogous gene, MYB88, overlaps with FLP function in generating normal stomatal patterning. Plants homozygous for mutations in both genes exhibit more severe defects than flp alone, and transformation of flp plants with a genomic MYB88 construct restores a wild-type phenotype. Both genes compose a distinct and relatively basal clade of atypical R2R3 MYB proteins that possess an unusual pattern of amino acid substitutions in their putative DNA binding domains. Our results suggest that two related transcription factors jointly restrict divisions late in the Arabidopsis thaliana stomatal cell lineage.